Poly(3,4-ethylenedioxythiophene/permethylated β-cyclodextrin) polypseudorotaxane and polyrotaxane: Synthesis, characterization and application as hole transporting materials in perovskite solar cells - Thitirat Putnin (2018)
© 2018 Poly(3,4-ethylenedioxythiophene/permethylated β-cyclodextrin) polypseudorotaxane (PEDOT⋅TMβCD) (P1) was synthesized by the chemical oxidation of 3,4-ethylenedioxythiophene (EDOT) as an inclusion complex with 2,3,6-tri-O-methyl β-cyclodextrin (TMβCD) (EDOT·TMβCD) with a five-fold excess of iron (III) chloride oxidant over the stoichiometric amount in water. The obtained P1 was converted to its P2 polyrotaxane by the end capping of the PEDOT backbones with bulky triphenylmethane to avoid the dethreading of TMβCD. The chemical structures of P1 and P2 were proved by FT-IR and1H NMR spectroscopy. The coverage ratios of the P1 and P2 chains were found to be 43.7 ± 5.2% and 27.1 ± 2.8%, respectively. Rotaxane formation results in improvements of the solubility in common organic solvents, as well better film forming ability combined with a high transparency. The UV–Vis absorption of P2 in C6H5Cl/CHCl3(1/1 v/v) exhibits a hypsochromic shift of 4 nm compared with P1. Atomic force microscopy, AFM, indicated that the P1 film is more uniformly distributed over the substrate area compared to that of the P2, although both surfaces have the roughness parameter values close to 2.90 nm. The newly synthesized compounds were then applied as dopant/additive-free hole transport materials in perovskite solar cells. P1 exhibited a photovoltaic performance of 5.54% under 1 sun illumination, whereas P2 showed a lower efficiency (3.8%) attributed to its lower photocurrent density. These performances are comparable to those obtained for control devices using as hole transporter spiro-OMeTAD (6.27% as dopant/additive-free hole transport material, 14.41% in LiTFSI and tert-butylpyrridine doped system).